Meeting the psychoeducational needs of minority students : evidence-based guidelines for school psychologists and other school personnel - Frisby, Craig L. (Hoboken, New Jersey : Wiley, 2013)
"Dr. Frisby focuses a bright light on issues that often remain obscured in a fog of polemics, deeply held convictions, and genuine concern for the plight of minority students. iMeeting the Psychoeducational Needs of Minority Students /icuts through this fog with intense, sharp, clear thinking and data, driven conclusions." 'Jeffrey P. Braden, PhD, Professor of Psychology and Dean of the College of Humanities and Social Sciences, North Carolina State University/ "Going beyond superficial 'feel good' or 'feel bad' ideologies to probe what really makes a difference in meeting the needs of often underserved populations, Craig Frisby provides a comprehensive, rigorous, well, written, and entertaining (honest!) work that addresses the intersection of race, ethnicity, and education." 'Betty Henry, PhD, School Psychologist, California School for the Blind "Dr. Frisby makes a perceptive and incisive assessment of much of the multicultural ideology currently propagated in professional psychology and education and directly confronts some of the major issues surrounding multiculturalism. Unlike many other critiques that have been proffered over the last few decades, however, iMeeting the Psychoeducational Needs of Minority Students /ialso provides many concrete solutions for how to begin changing the current milieu." 'A. Alexander Beaujean, PhD, Associate Professor, Baylor University bA practical, research, based guide to facilitating positive educational outcomes for racial, ethnic, and language minority students/b This timely book is written from the perspective of contemporary school psychology for a variety of school personnel, including school psychologists, teachers, guidance counselors, and administrators, with coverage of:ulliThe problem of quack multiculturalism/liliHome and family/liliContext for school learning/liliGeneral cognitive ability, learning, and instruction/liliTesting and assessment/liliSchool discipline and behavior management/liliCrime, delinquency, and gangs/liliSchool district resources/li/ul.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: School psychologists; Minority students -- Counseling of; EDUCATION -- Counseling -- Crisis Management; Minority students -- Counseling of; School psychologists; Electronic books; Electronic books